A revision of the genus Notothylas (Notothyladaceae, Anthocerotophyta) in China - Peng, Tao; Zhu, Rui-Liang (Phytotaxa, 2013)
The genus Notothylas in China contains four species. One new species, Notothylas yunnanensis, is described and illustrated. The new species is characterized by each proximal spore surface with a small central hollow, irregularly arranged, rectangular to quadrate epidermal cells of the capsule, and absence of a special dehiscence line in the capsule. A key to the species of Notothylas in China is provided.